Water footprint: An effective tool for the challenge of water sustainability (2020)
(Eng) Water is an indispensable liquid for subsisting as for the development of society. However, currently the availability of water refers to the world community, at the same time, to the physi cal and economic problems of the resource, reason why it is necessary that this resource has an efficient management of the way to satisfy the current needs, without compromising its use in the future. This article will present a conceptual analysis of the dynamics of the resource with the emphasis on scarcity, and the importance of integral management, around an indicator such as the water footprint, the view as an effective tool for decision making